Prevalence, characteristics, management, and outcome of pulmonary tuberculosis in HIV-infected children in the TREAT Asia pediatric HIV observational database (TApHOD) - Tavitiya Sudjaritruk (2018)
A multicenter, retrospective, observational study was conducted to determine prevalence, characteristics, management, and outcome of pulmonary tuberculosis (PTB) in Asian HIV-infected children in the TREAT Asia Pediatric HIV Observational Database (TApHOD). Data on PTB episodes diagnosed during the period between 12 months before antiretroviral therapy (ART) initiation and December 31, 2009 were extracted. A total of 2678 HIV-infected children were included in TApHOD over a 13-year period; 457 developed PTB, giving a period prevalence of 17.1% (range 5.7-33.0% per country). There were a total of 484 PTB episodes; 27 children had 2 episodes each. There were 21 deaths (4.3%). One third of episodes (n=175/484) occurred after ART initiation at a median of 14.1 months (interquartile range [IQR] 2.5-28.8 months). The median (IQR) CD4+ values were 9.0% (3.0-16.0%) and 183.5 (37.8-525.0) cells/mm 3 when PTB was diagnosed. Most episodes (n=424/436, 97.3%) had abnormal radiographic findings compatible with PTB, whereas half (n=267/484, 55.2%) presented with clinical characteristics of PTB. One third of those tested (n=42/122, 34.4%) had bacteriological evidence of PTB. Of the 156 episodes (32.2%) that were accompanied with extrapulmonary TB, pleuritis was the most common manifestation (81.4%). After treatment completion, most episodes (n=396/484, 81.9%) were recorded as having positive outcomes (cured, treatment completed and child well, and improvement). The prevalence of PTB among Asian HIV-infected children in our cohort was high. Children with persistent immunosuppression remain vulnerable to PTB even after ART initiation. © 2013 Mary Ann Liebert, Inc.